Psiko-edukasi kesehatan reproduksi pada remaja melalui pemberdayaan influencer media sosial - Rustam, Husnul Khotimah; Syamson, Meriem Meisyaroh; Nurdin, Nasrayanti; Herikzah, Ramli; Murtini, Murtini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: This reproductive health psychoeducation program, designed to enhance positive emotions and self-confidence among adolescents using social media influencers, is designed as a promotive-preventive effort to address the developmental challenges of adolescents who are vulnerable to misinformation about reproductive health. The program's background is based on the low reproductive health literacy among adolescents and the high influence of social media on the behavior and mindset of the younger generation. Purpose: To increase adolescents' understanding of reproductive health, build awareness of the importance of self-care, and foster positive emotions and self-confidence through the empowerment of influencers and digital media. Method: This activity was carried out in June 2025 at SMAN 2 Sidenreng Rappang with a population of 120 people while the sample size was 46 people. The material delivery technique was through lectures interspersed with ice breaking. The method of implementing this reproductive health psycho-education program used a social media-based educational approach with collaboration with influencers close to the youth segment. The first stage was conducting a needs analysis, followed by selecting influencers, then producing psycho-educational content, followed by implementation and digital interaction, then conducting program evaluation and analyzing digital engagement (number of views, likes, comments, and participation). This method is designed to be participatory, interactive, and relevant to the digital world of youth, so that psycho-educational messages can be optimally received. Results: The majority of participants demonstrated a better understanding of basic reproductive health concepts, the risks of risky sexual behavior, and the importance of maintaining reproductive health. Positive emotions increased, including feelings of calmer, more motivated, and more optimistic about the physical and social changes they experienced. Adolescents demonstrated greater courage in expressing their opinions, rejecting calls to engage in risky behavior, and making healthy decisions. Participant engagement on social media increased, as evidenced by the high number of views, likes, comments, and participation in online discussions. Conclusion: A social media-based reproductive health psychoeducation program involving influencers has proven to be an innovative and effective approach to improving health literacy, building positive emotions, and fostering self-confidence in adolescents. This activity increased adolescents' understanding, positive attitudes, and courage in making healthy decisions. It also contributes to the development of technology-based educational strategies that are relevant in the digital era and can be replicated across regions. Suggestion: For the program's sustainability, it is recommended that psycho-educational content be continuously developed in more varied and creative formats to attract adolescents in the long term. It is hoped that this program will not be merely a temporary intervention, but can become a model for sustainable reproductive health education with broad impact, supporting the development of a healthy, confident, and psychologically well-being generation. Keywords: Adolescents; Positive emotions; Reproductive health psycho-education; Social media influencers; Self-confidence Pendahuluan: Program psiko-edukasi kesehatan reproduksi untuk meningkatkan emosi positif dan kepercayaan diri remaja menggunakan peran influencer media sosial dirancang sebagai upaya promotif-preventif dalam menghadapi tantangan perkembangan remaja yang rentan terhadap informasi keliru mengenai kesehatan reproduksi. Latar belakang program ini didasari oleh rendahnya literasi kesehatan reproduksi pada remaja serta tingginya pengaruh media sosial terhadap perilaku dan pola pikir generasi muda. Tujuan: Untuk meningkatkan pemahaman remaja tentang kesehatan reproduksi, membangun kesadaran akan pentingnya menjaga diri, menumbuhkan emosi positif dan rasa percaya diri melalui pemberdayaan influencer dan media digital. Metode: Kegiatan ini dilaksanakan pada Juni 2025 yang bertempat di SMAN 2 Sidenreng Rappang dengan populasi sebesar 120 orang sementara jumlah sampel sebanyak 46 orang. Teknik penyampaian materi adalah dengan ceramah dan diselingi dengan ice breaking. Metode pelaksanaan program psiko-edukasi kesehatan reproduksi ini menggunakan pendekatan edukasi berbasis media sosial dengan kolaborasi influencer yang dekat dengan segmen remaja. Tahap pertama melakukan analisis kebutuhan selanjutnya melakukan pemilihan influencer kemudian produksi konten psiko-edukasi yang dilanjutkan dengan implementasi dan interaksi digital, kemudian melakukan evaluasi program serta analisis keterlibatan digital (jumlah views, likes, komentar, dan partisipasi). Metode ini dirancang agar bersifat partisipatif, interaktif, dan relevan dengan dunia digital remaja, sehingga pesan psiko-edukasi dapat diterima secara optimal. Hasil: Mayoritas peserta menunjukkan pemahaman yang lebih baik mengenai konsep dasar kesehatan reproduksi, risiko perilaku seksual berisiko, serta pentingnya menjaga kesehatan organ reproduksi. Adanya peningkatan emosi positif berupa perasaan lebih tenang, termotivasi, serta lebih optimis dalam memandang perubahan fisik dan sosial yang mereka alami. Remaja menunjukkan keberanian yang lebih besar dalam menyampaikan pendapat, menolak ajakan berperilaku berisiko, serta mengambil keputusan sehat. Keterlibatan (engagement) peserta dalam media sosial meningkat, ditunjukkan oleh tingginya jumlah views, likes, komentar, serta partisipasi dalam diskusi online. Simpulan: Program psiko-edukasi kesehatan reproduksi berbasis media sosial dengan melibatkan peran influencer terbukti menjadi pendekatan inovatif dan efektif dalam meningkatkan literasi kesehatan, membangun emosi positif, serta menumbuhkan kepercayaan diri remaja. Kegiatan ini memberikan peningkatan pemahaman, sikap positif, serta keberanian remaja dalam mengambil keputusan sehat dan juga memberikan kontribusi pada pengembangan strategi edukasi berbasis teknologi yang relevan di era digital serta dapat direplikasi di berbagai wilayah. Saran: Untuk keberlanjutan program, disarankan agar konten psiko-edukasi terus dikembangkan dengan format yang lebih variatif dan kreatif, agar menarik minat remaja dalam jangka panjang. Diharapkan program ini tidak hanya menjadi intervensi sesaat, tetapi dapat menjadi model edukasi kesehatan reproduksi yang berkelanjutan, berdampak luas, serta mendukung terbentuknya generasi muda yang sehat, percaya diri, dan memiliki kesejahteraan psikologis yang lebih baik.